The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1182/blood-2006-09-045807
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow CD8 cells down-modulate membrane IL-7Rα expression and exhibit increased STAT-5 and p38 MAPK phosphorylation in the organ environment.

Abstract: By comparing mature CD8-cell turnover in different organs, we previously demonstrated that CD8 cells proliferate predominantly in the bone marrow (BM). To investigate the mechanisms underlying such increased turnover, we compared BM, lymph nodes, and spleen CD8 cells from untreated C57BL/6 mice regarding in vivo proliferation within the organ; in vitro response to interleukin-7 (IL-7), IL-15, IL-21; ex vivo expression of membrane CD127 (IL-7Ralpha), intracellular Bcl-2, phospho-STAT-5 (signal transducer and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
45
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(56 citation statements)
references
References 60 publications
11
45
0
Order By: Relevance
“…This finding not only argues against the possibility that GITR hi and GITR lo cells are different subsets of T cells within the spleen versus bone marrow, or that IL-15 is required to maintain a unique subset of memory T cells that is resident in the bone marrow, but rather it suggests that GITR upregulation in the bone marrow reflects the local microenvironment. Our data concur with studies from Di Rosa and colleagues (21,22), which indicate that despite the lack of recent Ag exposure, bone marrow CD8 memory T cells have a more activated phenotype than do their counterparts in other organs. They also demonstrated that although homeostatic proliferation is augmented in the bone marrow, CD8 memory T cells in this organ do not have an intrinsic ability for enhanced cytokine-mediated proliferation, suggesting that they are stimulated to proliferate locally in the bone marrow (21).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This finding not only argues against the possibility that GITR hi and GITR lo cells are different subsets of T cells within the spleen versus bone marrow, or that IL-15 is required to maintain a unique subset of memory T cells that is resident in the bone marrow, but rather it suggests that GITR upregulation in the bone marrow reflects the local microenvironment. Our data concur with studies from Di Rosa and colleagues (21,22), which indicate that despite the lack of recent Ag exposure, bone marrow CD8 memory T cells have a more activated phenotype than do their counterparts in other organs. They also demonstrated that although homeostatic proliferation is augmented in the bone marrow, CD8 memory T cells in this organ do not have an intrinsic ability for enhanced cytokine-mediated proliferation, suggesting that they are stimulated to proliferate locally in the bone marrow (21).…”
Section: Discussionsupporting
confidence: 92%
“…Our data concur with studies from Di Rosa and colleagues (21,22), which indicate that despite the lack of recent Ag exposure, bone marrow CD8 memory T cells have a more activated phenotype than do their counterparts in other organs. They also demonstrated that although homeostatic proliferation is augmented in the bone marrow, CD8 memory T cells in this organ do not have an intrinsic ability for enhanced cytokine-mediated proliferation, suggesting that they are stimulated to proliferate locally in the bone marrow (21). This is con- hi T cells recovered from each organ was determined.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We characterized some of the molecular events occurring in CD8 T cells within the BM, such as increased phosphorylation of the signal-transducing molecules STAT-5 and p38 MAPK and reduced membrane expression of CD127, the IL-7R ␣-chain (5). Both naive-phenotype CD44 int/low and memory-phenotype CD44 high CD8 T cells contain a higher percentage of proliferating cells in the BM than in spleen and LN (5). The important role played by the BM in mature CD8 T cell turnover becomes even more evident when the total numbers of proliferating CD8 T cells contained in the sum of spleen, LN, and BM are taken into account.…”
mentioning
confidence: 90%
“…Of particular interest is the BM, in which a significantly increased number of these cells was found compared with WT memory T cells. It has been shown that the survival factors IL-7 and IL-15 are expressed in the BM (23,34,35). In addition, memory CD8 T cells are reported to use IL-15 in the BM to turn over (23).…”
Section: Ccr7 Ko Memory T Cells Showed Faster Homeostatic Proliferatimentioning
confidence: 99%